Selective disappearance does not underlie age-related changes in trait repeatability in red squirrels. (1st March 2021) - Martinig, April Robin; Mathot, Kimberley J; Lane, Jeffrey E; Dantzer, Ben; Boutin, Stan
Abstract: Understanding the causes and consequences of repeatable among-individual differences in behavior (i.e., animal personality) is a major area of research in behavioral and evolutionary ecology. Recently, attention has turned to understanding the processes behind changes in repeatability through ontogeny because of their implications for populations. We evaluated the relative importance of selective disappearance (i.e., differential mortality), an among-individual mechanism, in generating age-related changes in the repeatability of aggression and activity in juvenile North American red squirrels ( Tamiasciurus hudsonicus ). We observed age-related decreases in the repeatability of aggression across ages, arising from lower among-individual variance. Although we found evidence for directional selection on aggressiveness, it was insufficient to erode among-individual variance. Thus, ontogenetic decreases in the repeatability of aggression do not appear to be due to selective disappearance. In contrast, the repeatability of activity was higher across ages due to higher among-individual variance in activity, but there was no support for selective disappearance based on activity. Taken together, our results suggest that age-related changes in trait repeatability in red squirrels are not the result of selective disappearance and instead may be the result of within-individual developmental processes, such as individual differences in developmental trajectories. Abstract : Surviving to adulthood is no easy task for juvenile red squirrels. How you behave can be especially telling for your survival. Surprisingly, active and aggressive juvenile red squirrels appeared to survive just as well as their more subdued counterparts. Instead, adaptability or fluctuating selection may be at work behind the scenes.